Correlations between some quantitative traits of cucumber F1 parthenocarpic hybrids with a smooth fruit type grown in plastic greenhouses - N. N. Khomchenko; V. N. Shevkunov (Овощи России, 2023)
Relevance. The study of correlations between cucumber traits makes it possible to conduct a preliminary assessment of plants more objectively, to identify forms with high economically valuable traits, and their comprehensive assessment will make it possible to select the best source material for further selection.Methodology. In 2021, in the Crimean SC "Gavrish", experiments were laid with 24 parthenocarpic F1 hybrids of the smooth type in two repetitions, 8 plants each. Cucumber was grown in a film greenhouse on soils in spring-summer turnover. Cultivation technology – in accordance with the requirements adopted in the region. The evaluation of economically valuable traits was performed according to the generally accepted method.Results. During the correlation analysis, high, medium positive and negative relationships were established between the individual main economic characteristics of the parthenocarpic cucumber when grown in an unheated film greenhouse. The method of correlation analysis revealed a significantly high correlation between the degree of branching by determinant lateral shoots and the number of fruits per node (r=0.84), the number of female flowers per plant (r=0.72) and the number of fruits per plant (r=0.68). Fruit length and index are highly negatively correlated with the number of fruits per plant (r=-0.86) and the number of female flowers per plant (r=-0.84…-0.85). A high correlation appears between weight, length, fruit shape index and the number of fruits in a node (r=-0.75...-0.76).The trait commercial yield significantly negatively correlates with the trait length of internodes on the main shoot (r=-0.64…-0.68).